An Aqueous-Ethanol Extract of Liriope spicata var. prolifera Ameliorates Diabetic Nephropathy through Suppression of Renal Inflammation. (20th August 2013) - Lu, Hung-Jen; Tzeng, Thing-Fong; Hsu, Jui-Chin; Kuo, Shih-Hao; Chang, Chia-Hsin; Huang, Shin-Ya; Chang, Fang-Yu; Wu, Ming-Chang; Liu, I-Min
Abstract : The tuberous root of Liriope spicata var. prolifera (TRLS; Liliaceae family) is valued for the ability to promote glucose homeostasis, and it may therefore be utilized as an adjuvant therapy in the control of diabetic complications. The aim of the present study was to examine the effects of an aqueous ethanol extract from TRLS (TRLS-ext) (100 or 200 mg kg −1 per day for eight weeks) on rats with streptozotocin-induced diabetic nephropathy (DN). Renal dysfunction in diabetic rats was ameliorated by TRLS-ext as evidenced by reduced creatinine clearance, as well as increased blood urea nitrogen and proteinuria. Treatment with TRLS-ext was found to markedly improve histological architecture in the diabetic kidney. Hyperglycemia induced degradation of inhibitory kappa B and reduced nuclear factor kappa B activation, leading to increased infiltration of macrophages and increased levels of proinflammatory cytokines, including interleukin-1 and tumor necrosis factor- α . All of the above abnormalities were reversed by TRLS-ext treatment, which also decreased the expression of intercellular adhesion molecule-1, monocyte chemoattractant protein-1, and fibronectin in the diabetic kidneys. These findings provide a perspective on the renoprotective effects of TRLS-ext in DN.